2009
DOI: 10.1002/marc.200900561
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Initiated PLP‐SEC of Butyl Acrylate and Styrene from Silica Nanoparticles

Abstract: The pulsed-laser polymerization size-exclusion chromatography (PLP-SEC) technique has been successfully applied to the measurement of the propagation rate coefficient, k(p) , of the surface-initiated polymerizations of butyl acrylate (BA) and styrene, using the silica-immobilized bipedal initiator 4,4'-azobis(4-cyano-N-(3″-triethoxysilylpropyl)-valeric amide) (ACTA). The molecular weight distribution (MWD) of grafted poly(BA) polymerized at 25 °C was structureless, whereas at 5 °C reaction temperature, the MWD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…They concluded that the termination is heavily influenced when initiating the polymerization from surfaces instead of in solution, but no quantitative information has been given. Recently, we applied the pulsed-laser polymerization–size-exclusion chromatography (PLP-SEC) method in order to obtain information about the propagation kinetics of surface-tethered macroradicals . We found that the propagation rate coefficient, k p , of surface-bound radicals is slightly enhanced in comparison to free macroradicals, which may be indication of the fact that that the growing chains are not able to shield the active center as well as the macroradicals in solution, due to their surface anchorage.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the termination is heavily influenced when initiating the polymerization from surfaces instead of in solution, but no quantitative information has been given. Recently, we applied the pulsed-laser polymerization–size-exclusion chromatography (PLP-SEC) method in order to obtain information about the propagation kinetics of surface-tethered macroradicals . We found that the propagation rate coefficient, k p , of surface-bound radicals is slightly enhanced in comparison to free macroradicals, which may be indication of the fact that that the growing chains are not able to shield the active center as well as the macroradicals in solution, due to their surface anchorage.…”
Section: Introductionmentioning
confidence: 99%
“…This straightforward approach enables insight into radical propagation kinetics from a solid support, which could only be indirectly assessed beforehand. [33] The determined p k values presented in this thesis (chapter 4) [152] are substantially higher than given IUPAC data. [67,155] Possible causes are presented such as a reduced shielding of the radical site, which could be related to the chain-length dependence of p k .…”
Section: Closing Remarksmentioning
confidence: 58%
“…In this chapter the determination of p k values for surface-initiated polymerizations of nBA and styrene via the state-of-the-art PLP-SEC method is presented along with reference experiments, in which DMPA and 2,2′-azo-bis-(iso-butyronitrile) (AIBN) were applied as initiators in solution (Scheme 4-1). [152] Since its invention in the 1980's, [64] the PLP-SEC technique has been applied to various polymerization systems including polymerizations of numerous monomers in bulk, [67,[153][154][155] copolymerizations, [156][157][158] polymerizations at varying temperatures and pressures, [159] polymerizations in different solvents [160] such as water, [161][162][163][164][165] supercritical CO 2 , [166][167][168][169] and ionic liquids, [170,171] as well as in heterogeneous media. [172,173] Surprisingly, a field which has not yet been in the focus of the PLP-SEC method is the one of surface-initiated polymerizations, which has generally received increasing attention in recent years due to the ability to produce tailored surfaces and materials with remarkable properties.…”
Section: Surface-initiated Polymerizations 4 Surface-initiated Plp-secmentioning
confidence: 99%